E-Governmet : Pilar Transparansi dan Akuntabilitas Pemerintahan Desa (Studi Kasus Desa Baureno Kecamatan Jatirejo Kabupaten Mojokerto) - Dian Wijaya (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
In the presence of the Covid-19 pandemic in Indonesia, many aspects have changed, especially the government aspect. The government is required to issue the latest policies regarding the handling of the Covid-19 pandemic itself. In the village ministry, the village ministry issued the latest policy, namely Permendes No. 6 of 2024 which was not followed up by the village government, in this case the Baureno village government issued several policies. The benefits of this study itself are as information material to find out and analyze the Implementation of Permendes No. 6 of 2024 in the Priority Use of Village Funds in 2024 in Baureno Village, Jatirejo District, Mojokerto Regency. If we relate it to the theory of policy implementation from Merilee S Grindle, there are six aspects that need to be seen, of the six aspects conveyed, this policy implementation theory is very related.Based on the research results that have been obtained through several informants, the implementation of Permendes No. 6 of 2024 in the priority use of village funds in 2024 in Baureno Village with program efforts that can create good conditions. The results of the study prove that the Baureno village community is satisfied with the efforts of the Baureno village government in issuing policies related to Permendes No. 6 of 2024.